Nitazoxanide potentiates linezolid against linezolid-resistant Staphylococcus aureus in vitro and in vivo. (24th June 2022) - Kaul, Grace; Akhir, Abdul; Shukla, Manjulika; Rawat, Kundan S; Sharma, Chandra P; Sangu, Komal G; Rode, Haridas B; Goel, Atul; Chopra, Sidharth
Abstract: Background: Antimicrobial resistance is a growing menace, claiming millions of lives all over the world. In this context, drug repurposing is one approach gaining interest as a suitable alternative to conventional drug discovery and development. Methods: Whole-cell assays were used to screen FDA-approved drugs to identify novel antimicrobial agents active against bacterial pathogens. Following identification of nitazoxanide, its various characteristics, such as antimicrobial activity against MDR isolates, time–kill kinetics, ability to synergize with approved drugs, antibiofilm activity and ability to generate resistance in Staphylococcus aureus, were determined, followed by determination of its in vivo potential against MDR S. aureus . Results: Nitazoxanide demonstrated a potent in vitro antistaphylococcal profile, including equipotent activity against clinical drug-resistant S. aureus and Enterococcus spp. Nitazoxanide exhibited concentration-dependent killing, significantly eradicated preformed S. aureus biofilm and S. aureus did not generate resistance to it. Nitazoxanide strongly synergized with linezolid both in vitro and in vivo against linezolid-susceptible and -resistant S. aureus, displaying superior activity to untreated control and drug-alone treatment groups. Conclusions: Nitazoxanide can be utilized in combination with linezolid against infections caused by linezolid-resistant S. aureus as it exhibits strong synergism in vitro and in vivo .